Acculturation of Personality: A Three-Culture Study of Japanese, Japanese Americans, and European Americans. (July 2013) - Güngör, Derya; Bornstein, Marc H.; De Leersnyder, Jozefien; Cote, Linda; Ceulemans, Eva; Mesquita, Batja
The present study tests the hypothesis that involvement with a new culture instigates changes in personality of immigrants that result in (a) better fit with the norms of the culture of destination and (b) reduced fit with the norms of the culture of origin. Participants were 40 Japanese first-generation immigrants to the United States, 57 Japanese monoculturals, and 60 U.S. monoculturals. All participants completed the Jackson Personality Inventory as a measure of the Big Five; immigrants completed the Japanese American Acculturation Scale. Immigrants' fits with the cultures of destination and origin were calculated by correlating Japanese American mothers' patterns of ratings on the Big Five with the average patterns of ratings of European Americans and Japanese on the same personality dimensions. Japanese Americans became more "American" and less "Japanese" in their personality as they reported higher participation in the U.S. culture. The results support the view that personality can be subject to cultural influence.